Les rapports de l’art abstrait (Kandinsky, Klee, Mondrian) avec les tendances d’abstraction de l’art sacré / The Connections of Abstract Art (Kandinsky, Klee, Mondrian) with the Abstractization Tendencies of Sacred Art - Gabriel Badea (Anastasis: Research in Medieval Culture and Art, 2016)
The main purpose of this paper is to study the connections that can be established between the modern abstractionism and the abstract tendencies from other historical eras. In the first part I will present three distinct interpretations: the first direction is based on authors as Mircea Eliade and Roger Lipsey, who see modern art through the links still alive between art and religion, from a syncretic perspective, or, after Eliade’s expression, based on a creative hermeneutics. The second direction is represented by the work of Adorno, Compagnon, Greenberg, Lyotard, for whom the modern art is a manifestation of radical discontinuity in relation to the art of the past, and the emergence of abstractionism is due primarily to a historical necessity (the increasing rupture between form and content, the increased autonomy of the sensible over the intelligible). The third direction is represented to Wilhelm Worringer, whose work (Abstraktion und Einfühlung, 1907) predates the emergence of the first abstract paintings, but relying on the German aesthetic tradition, manages to go beyond the threshold distinction between figurative and abstract, thus identifying a type of Einfühlung art and another of abstract type, namely the predominance of one or the other in different historical contexts and civilizational patterns. In the second part of the paper I will refer to instances of the spirit of abstraction in the case of Byzantine sacred art, especially in the footsteps of Plotinian aesthetics and as a result of the iconoclastic crisis. In the last part, I will present the key ideas for three major representatives of abstractionism (Kandinsky, Klee, Mondrian) and the survival of the concepts of sacred art in their works and art theories.